Bilingual Language Control Flexibly Adapts to Cultural Context - Liu, Cong; Li, Lu; Jiao, Lu; Wang, Ruiming (Frontiers in Psychology, 2021)
How does bilingual language control adapt to the cultural context? We address this question by looking at the pattern of switch cost and reversed language dominance effect, which are suggested to separately reflect reactive and proactive language control mechanisms, in the contexts with culturally-neutral pictures (i.e., baseline context) or culturally-biased pictures (i.e., congruent context where culture matched the language to be spoken or incongruent context where culture mismatched the language to be spoken). Results showed an asymmetric switch cost with larger costs for L2 in the congruent context as compared with the baseline and incongruent contexts, but the reversed language dominance effect was not changed across contexts, suggesting that cultural context plays a critical role in modulating reactive but not proactive language control. These findings reveal the dynamic nature of language control in bilinguals and have important implications for the current models of bilingual language control.